2015
DOI: 10.1038/cddis.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide promotes beta-cell regeneration and survival through regulating β-catenin/TCF7L2 pathway

Abstract: T-cell factor 7-like 2 (TCF7L2) is an important transcription factor of Wnt/β-catenin signaling, which has critical roles in β-cell survival and regeneration. In preliminary screening assay, we found geniposide, a naturally occurring compound, was able to increase TCF7L2 mRNA level in Min6 cells. Here we aimed to investigate the role of geniposide in β-cell and underlying mechanism involved. Geniposide was found to promote β-cell survival by increasing β-cell proliferation and decreasing β-cell apoptosis in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…GLP-1, a gut hormone, and GLP-1 analogs have beneficial effects on cardiovascular system by inhibiting cardiomyocyte apoptosis during I/R [23,[40][41][42][43]. It has been reported that geniposide, as a novel GLP-1R agonist, exerts different protective effects by activating GLP-1R in various tissues [15][16][17][18][19]. GLP-1R is expressed in various tissues and organs, including the pancreas, gastrointestinal tract, nervous system, blood vessels, and heart [44,45]..…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1, a gut hormone, and GLP-1 analogs have beneficial effects on cardiovascular system by inhibiting cardiomyocyte apoptosis during I/R [23,[40][41][42][43]. It has been reported that geniposide, as a novel GLP-1R agonist, exerts different protective effects by activating GLP-1R in various tissues [15][16][17][18][19]. GLP-1R is expressed in various tissues and organs, including the pancreas, gastrointestinal tract, nervous system, blood vessels, and heart [44,45]..…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide, an extract of Gardenia jasminoides J. Ellis and a novel agonist for glucagon-like peptide-1 receptor (GLP-1R), has been shown to exert antinociception effects [15], promote β-cell regeneration, attenuate β-cell apoptosis [16,17], regulate insulin secretion in INS-1 cells [18], and prevent oxidative stress of PC12 cell [19]. Accumulating evidences has revealed that glucagon-like peptide 1 (GLP-1) and GLP-1 analogues exert anti-apoptotic effects by activating GLP-1R via the phosphatidylinositol 3 kinase (PI3K)/ AKT signaling pathway [3,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies implicated β-cell dysfunction as the underlying cause of diabetes in patients with the TCF7L2 risk variant [2][3][4][5] and have suggested that Wnt signalling plays an important role in both pancreatic development and in the function of mature pancreatic islets [6]. The activation of the canonical Wnt pathway, by ligands such as Wnt3a, has been of particular interest as it can increase β-cell proliferation, decrease apoptosis and improve glucose stimulated insulin secretion [6][7][8][9][10][11][12]. However there is now increasing evidence that non-canonical Wnt ligands such as Wnt4 can antagonise the signalling mediated by Wnt3a and may play an equally important role in β-cell function [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…TCF7L2 influences b-cell functions by affecting b-cell survival in pancreatic islets. Yao et al [29] identified a novel role of geniposide in promoting b-cell survival and regeneration by mechanisms involving the activation of b-catenin/TCF7L2 signaling. The carriers of an at-risk allele in TCF7L2 are thought to be more susceptible to T2DM, since active TCF7L2 might be essential for pancreatic b-cells proliferation.…”
Section: B-cell Apoptosis Proinsulin Conversion and B-cell Responsivitymentioning
confidence: 99%
“…The African Americans Y Sale et al [13] b-cell apoptosis increased with the decrease of active TCF7L2, which influenced the insulin secretion eventually. Finding a way to prevent the apoptosis of b-cells may be a possible treatment for T2DM, like the use of geniposide [29]. The prohormone precursor to insulin, proinsulin, is produced in the b-cells of the islets, specialized regions of the pancreas.…”
Section: B-cell Apoptosis Proinsulin Conversion and B-cell Responsivitymentioning
confidence: 99%